(untitled) (Research, Society and Development, 2025)
The objective of this study was, through an integrative review, to assess whether changes in salivary components in patients with cerebral palsy can serve as predictive factors for the occurrence of dental caries and periodontal disease. Alterations in saliva components are common in individuals with cerebral palsy (CP) and may increase the risk of developing dental caries and periodontal disease. An integrative literature review was conducted following six methodological steps: defining the topic based on the established objectives, setting inclusion and exclusion criteria for articles, collecting and organizing data from the selected studies, evaluating the methodologies used in the research, interpreting and contextualizing the obtained results, and presenting, arguing, and reviewing the selected studies. From data analysis, it was observed that changes in salivary components, such as elevated salivary osmolarity values, negatively affect saliva’s buffering capacity, favoring dental caries. Increased cytokine concentration is associated with the progression of periodontal disease, indicating a relationship between salivary inflammatory responses and the severity of oral diseases.